Efektivitas Bimbingan Kelompok Teknik Permainan Kata Dalam Meningkatkan Komunikasi Interpersonal Peserta Didik Kelas VII SMP Negeri 5 Surabaya - Nuriya, Noviya Wahyu; Wirastania, Aniek (Efektor, 2022)
The low level of interpersonal communication among students can cause adjustment difficulties. Communication is an essential component of daily activities. Communication will continue to be established with the people around you. One of the actions in improving interpersonal communication can be facilitating the learning process through fun guidance services. This study aimed to test the effectiveness of group guidance on word game techniques in improving students' interpersonal communication. This research is pre-experimental research with one group pre-test and post-test research design. The research method chosen is a quantitative research method with the help of an interpersonal communication measurement scale. The subjects used were students of class VII-A of SMP Negeri 5 Surabaya. Data analysis using SPSS Version 25 with non-parametric statistics Wilcoxon test. The study's results revealed that the indicators studied experienced a significant increase. This increase is seen from the difference in students' level of interpersonal communication. This shows that group guidance effectively improves students' interpersonal communication.